Topofilia e educação ambiental: estudo das percepções e representações ambientais da comunidade tradicional caiçara da Ilha Diana/Santos-SP - Rajab, Victor Pinto [UNIFESP] (2020)
The present case study aimed to investigate the perceptions and environmental representations of the traditional Caiçara community from Ilha Diana, located near the Port of Santos (Santos City, Sao Paulo State), in order to understand the problematics of socio-environmental and how it may threaten the permanence of the caiçara cultural identity. In order to conduct an integrated environmental analysis of the issue, this research was based on three dimensions: 1) Literature review on research already carried out about this community; 2) Field research structured in studies of environmental perception and representation, through the application of questionnaires to children who attend the Ilha Diana Municipal Municipal School (UME Rural - Ilha Diana) and to the elder residents of the community; 3) Elaboration of an Environmental Education proposal, based on the perception / representation studies. The survey included 25 participants in total, 14 children of 4 to 10 years old and 11 adults averaging 52 years. The approach used was qualitative and the techniques for analyzing the questionnaires were: drawing analysis, content analysis, and word cloud. The analyzes showed that the participants perceive the mangrove as an important provider of fishing resources, a representation framed as anthropocentric and naturalistic. At the same time, the participants realized the degradation caused by the port expansion process, which presupposes an understanding of the conflicting relationship between the Port of Santos and the mangrove. In addition, the participants reported an intense affective relationship to Ilha Diana, factors that help maintain cultural identity and encourage the feeling of belonging to the place. Finally, the proposed Environmental Education activity aimed to reconcile scientific and traditional knowledge about mangroves, seeking to bring children and adults closer to the community with the place they live and their history, in order to strengthen cultural identity and encourage them in the struggle for their traditional territory.